Contrasting responses of native and alien plant species to soil properties shed new light on the invasion of dune systems. (11th August 2020) - Vitti, Stefano; Pellegrini, Elisa; Casolo, Valentino; Trotta, Giacomo; Boscutti, Francesco
Abstract: Aims: Among terrestrial ecosystems, coastal sandy dunes are particularly prone to alien plant invasion. Many studies related the invasion of dune habitats to anthropic causes, but less is known about the role of soil properties and plant traits in plant invasion. In this study, we tested the relationships between soil features and alien plant invasion in dune systems, focusing on the interplay between soil nutrients, soil salinity and plant functional traits. Methods: Study sites were sandy barrier islands of the Marano and Grado lagoon (northern Adriatic Sea). One hundred plots (4 m × 4 m) were selected within 10 areas according to the main habitats occurring along the ecological gradient of dune system (foredune, backdune and saltmarsh). In each plot, we recorded all plant species occurrence and abundance and we collected a soil core. For each soil sample, soil texture, conductivity (as proxy of soil salinity), organic carbon and nitrogen content were analyzed and related to the species number and cover of native and alien plants. Variation of main reproductive and vegetative functional traits among habitats was also analyzed for both alien and native species. Important Findings: Soil properties were strongly related to overall plant diversity, by differently affecting alien and native species pools. In backdune, the most invaded habitat, a high soil conductivity limited the number of alien species, whereas the content of soil organic carbon increased along with alien plant abundance, suggesting also the occurrence of potential feedback processes between plant invasion and soil. We found a significant convergence between native and alien plant functional trait spectra only in backdune habitat, where environmental conditions ameliorate and plant competition increases. Our findings suggest that in harsh conditions only native specialized plants can thrive while at intermediate conditions, soil properties gradient acts in synergy with plant traits to curb/facilitate alien plant richness.